POPULARIZING THE EXISTANCE OF MALANG AND BATU WITH KIRANA TOUR AND TRAVEL - Lavenia Hariono; Elwin Graciano Lay; Sarah Maulida Primaputri (AIBPM Publisher, 2018)
The globalization era and the next decades are a crucial time for the relationship between tour and travel and sustainable development. The need to preserve the world’s inherent assets for future generations is becoming an imperative goal not only for tour and travel, but also for all other industries that use the earth’s natural resources. The scale of tour and travel’s contribution to the global economy and its potential for enabling sustainable development are becoming more real for governments, entrepreneurs, and others who involved in tour and travel industry. Nowadays, Tour and travel’s are tourism industries that become one of the largest industries in the world. Economically, it creates jobs and contributes to increase Gross Domestic Product (GDP), as well as brings in capital investment and exports. Socially and culturally, tour and traveloffers the opportunity of providing jobs for minority and disadvantaged groups, creating adequate training in management skills, education and technology to local people and increasing incomes in rural and local economies, thereby contributing to the alleviation of poverty in developing countries. Environmentally, it is essential for tour and travel to maintain an optimal balance of its natural resources to ensure the ongoing arrival of tourists to destinations. In Kirana Tour and Travels, marketing strategy will be based mainly on make sure customers know about the existence of Kirana and the services that Kirana’s give. Because the purpose is to make the right information available to the right target customers. This will be done through implementing a market penetration strategy that will make sure that Kirana’s tour and travel is well known and respected in the tourism industry. Kirana make sure that the prices take into consideration customers budgets, know that it exists, and how to contact Kirana. The marketing always communicate the sense of quality in every picture, every promotion, and every publication. Kirana’s promotional strategy will involve integrating advertising, events, personal selling, public relations, direct marketing and the Internet (specially in media social), details of which are provided in the marketing section of this plan.